2022
DOI: 10.1007/s12649-022-01838-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Aspergillus niger NRC1ami Pectinase Using Citrus Peel Pectin, Purification, and Thermodynamic Characterization of the Free and Modified Enzyme

Abstract: Enzyme cost and stability are the main problems facing industrial applications. Consequently, Aspergillus nigerNRC1ami was isolated from rotten orange and recorded a promising pectinase activity (13.8 U/ml). The enzyme was optimized using citrus peel pectin as the sole carbon source and recorded (40 U/ml). It was purified by two steps purifications and recorded 632 purification folds. The pure enzyme showed 14.7% carbohydrate content and consists of 15 amino acids. Glutamic acid was the major (22%) followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
(36 reference statements)
1
8
3
Order By: Relevance
“…26 The thermal stability of the enzyme isolated in this research was higher than previously reported based on the D -values comparison, which is higher than other research groups reported. 19,26…”
Section: Resultscontrasting
confidence: 74%
See 3 more Smart Citations
“…26 The thermal stability of the enzyme isolated in this research was higher than previously reported based on the D -values comparison, which is higher than other research groups reported. 19,26…”
Section: Resultscontrasting
confidence: 74%
“…28 The same relation between calculated ΔS and ΔH was reported previously for pectinase derived from A. niger isolated from orange, but the stability of this enzyme was low even after a chemical modification that resulted in a minimal increase in enzyme stability. 26 The thermal stability of the enzyme isolated in this research was higher than previously reported based on the D-values comparison, which is higher than other research groups reported. 19,26 The prevailing characterisation of PGs currently describes a predominant pattern of significantly low thermal stability.…”
Section: Papercontrasting
confidence: 74%
See 2 more Smart Citations
“…In paper industries, the enzymes are basically used for the manufacturing processes. In the present era of papermaking, the cationic polymers are used to improve drainage and increased retention of fine particles added to pulp in order to keep fines and filler. 153 The Alkaline peroxide bleaching of pulps solubilizes polysaccharides (pectins, or polygalacturonic acids), which are troublesome interfering substances.…”
Section: Applications Of Pectinasesmentioning
confidence: 99%